2019
DOI: 10.1016/j.patrec.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Neural network based reinforcement learning for audio–visual gaze control in human–robot interaction

Abstract: This paper introduces a novel neural network-based reinforcement learning approach for robot gaze control. Our approach enables a robot to learn and to adapt its gaze control strategy for human-robot interaction neither with the use of external sensors nor with human supervision. The robot learns to focus its attention onto groups of people from its own audio-visual experiences, independently of the number of people, of their positions and of their physical appearances. In particular, we use a recurrent neural… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 28 publications
0
57
0
1
Order By: Relevance
“…Moreover, the availability of suitable datasets would ease future research on this topic. In parallel, we wish to use this framework in the future as a tool to improve the decision process of a robotic system in a social context such as [5].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the availability of suitable datasets would ease future research on this topic. In parallel, we wish to use this framework in the future as a tool to improve the decision process of a robotic system in a social context such as [5].…”
Section: Resultsmentioning
confidence: 99%
“…However, we want to move away from feature engineering and formulate our human-robot interaction scenario as a deep reinforcement learning problem. Recent studies in HRI showed impressive results in employing deep reinforcement learning for various applications [14,15,12]. The main challenge for deep learning approaches is the lack of training data from human studies but we plan to tackle this problem using our current Bayesian-based model to simulate human behaviour data as a prior for the deep reinforcement learning model.…”
Section: Resultsmentioning
confidence: 99%
“…In deep networks, the selection of different hyper-parameters affects the accuracy of the algorithm [118]. This also applies to DRL, Lathuilière et al [86] presented several experiments to evaluate the impact of some of the principal parameters of their deep network structure. Thus far, model-free RL learning a value function or a policy through trial and error is the most commonly used approach in social robotics.…”
Section: Future Outlookmentioning
confidence: 99%